Optimizing the adaptation rate of feedlot steers dosed with Megasphaera elsdenii NCIMB 41125 and fed high starch diets - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.